2018
DOI: 10.1093/gji/ggy255
|View full text |Cite
|
Sign up to set email alerts
|

Trans-dimensional Bayesian inversion of airborne transient EM data from Taylor Glacier, Antarctica

Abstract: Conventional regularized nonlinear inversion methods for estimating electrical conductivity from observed electromagnetic data seek to find a single model that fits the data while minimizing a user-imposed model regularization norm. By contrast, Bayesian sampling techniques produce a large suite of models, all of which fit the data adequately, providing a wealth of statistical information about the model parameters. Importantly, this includes quantitative uncertainty estimates as well as any statistical proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…6a) improvement on their unconstrained equivalents). Note, imaging beneath a conductive structure is difficult for the TEM method due to the attenuated signal (Blatter et al, 2018); however our constrained inversion results show the bottom of the conductive layers (in (b) -(e) to be much better resolved, i.e. to within < 10 meters.…”
Section: Materials Resistivity Boundaries (ωM)mentioning
confidence: 80%
See 2 more Smart Citations
“…6a) improvement on their unconstrained equivalents). Note, imaging beneath a conductive structure is difficult for the TEM method due to the attenuated signal (Blatter et al, 2018); however our constrained inversion results show the bottom of the conductive layers (in (b) -(e) to be much better resolved, i.e. to within < 10 meters.…”
Section: Materials Resistivity Boundaries (ωM)mentioning
confidence: 80%
“…Synthetic TEM responses were calculated from the 1D block models using the Leroi forward modelling algorithm 10 (Raiche, 2008), then 5% normally distributed random noise was applied to all time gates, a similar noise model to Blatter et al (2018), see The inversions were run using resistivity ranges shown in Table 2 using a maximum depth of 80 m, consistent with the estimated maximum DOI for this configuration. To highlight the benefit of additional depth constraints, MuLTI-TEM is separately run for an unconstrained case, and a case in which the depths of snow-ice and ice-bed horizons are fixed.…”
Section: Data Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…For more robust and accelerated convergence, we implement parallel tempering (PT), whereby multiple Markov chains are run in parallel, each with its own 'temperature' T. The chains at T = 1 are unmodified and will make up the model ensemble; the chains at temperatures T > 1 explore a 'tempered' model space and, by swapping models with colder chains after each MCMC step, allow for more robust and accelerated convergence to the high probability regions of model space. For a detailed description of our algorithm see Blatter et al (2018), Ray et al (2013a) and Ray & Key (2012); for a helpful discussion of MCMC, see Gilks et al (1995); and for a thorough discussion of PT with numerical examples, see Sambridge (2013).…”
Section: Bayesian Joint Inversion Frameworkmentioning
confidence: 99%
“…The algorithm used in this work is the same as in Blatter et al (2018), except that here there is a water layer, which is sampled separately from the subsurface. At each step of the algorithm, a uniform random number is generated.…”
Section: Bayesian Joint Inversion Frameworkmentioning
confidence: 99%